NO2gas sensing of flame-made Pt-loaded WO3thick films - Thanittha Samerjai (2018)
Unloaded WO 3 and 0.25-1.0 wt% Pt-loaded WO 3 nanoparticles for NO 2 gas detection were synthesized by flame spray pyrolysis (FSP) and characterized via X-ray diffraction (XRD), scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). The BET surface area (SSA BET ) of the nanoparticles was measured by nitrogen adsorption. The NO 2 sensing properties of the sensors based on unloaded and Pt-loaded WO 3 nanoparticles were investigated. The results showed that the gas sensing properties of the Pt-loaded WO 3 sensors were excellent to those of the unloaded one. Especially, 0.25 wt% Pt-loaded WO 3 sensor showed highest response to NO 2 than the others at low operating temperature of 150 °C. © 2013 Elsevier Inc.